Unveiling Multidimensional Meanings: A Critical Analysis of Jungkook's "3D" Lyrics Using Fairclough's CDA Theory and Butler's Sexual Performativity Theory - Ellisa Indriyani Putri Handayani; Dewi Cahyaningrum; Sumarlam Sumarlam (Jurnal Onoma: Pendidikan, Bahasa, dan Sastra, 2024)
This article offers a in depth study of the lyrics of BTS's song "3D," employing Judith Butler's theory of gender performativity and Norman Fairclough's Critical Discourse Analysis as the research’s approaches. The study investigates how the song deviates from traditional masculine narratives by integrating components of worry and compassion into its portrayal of masculinity, offering an alternative conceptual framework for understanding gender roles. The findings highlight the role of the song in both support and questioning established gender standards, so illustrating the significant influence of media on the formation of masculinity. This study is limited to single song lyrics. It is necessary for further exploration into the portrayal of gender in media through diverse methodologies and active engagement with fan perspectives. This piece holds significant academic value as it contributes to the understanding of gender portrayal in media and its impact on societal gender norms.